Overview of Key Legal, Political, and Social Challenges Facing Global Vaccination Efforts (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
Despite the proven safety and effectiveness of vaccines, they are not utilized as widely as they should be. This article provides a high-level overview of five key challenges affecting the global vaccine uptake. First, availability is affected by the research costs and counterfeit vaccines. Second, accessibility is affected by distribution not being proportionate to need, and by poor infrastructure. Third, affordability is affected by intellectual property protections and costs of manufacturing and distribution. Fourth, appropriateness is affected by the way vaccine effectiveness varies and presents risks for immunocompromised populations. Fifth, acceptability is affected by controversies regarding risks and cultural objections.
Keywords: global vaccine uptake; vaccine availability; vaccine distribution; cold chain; anti-vaccination movement; herd immunity; vaccine hesitancy